High‐level production of human interleukin‐10 fusions in tobacco cell suspension cultures. Issue 5 (9th January 2013) - Kaldis, Angelo; Ahmad, Adil; Reid, Alexandra; McGarvey, Brian; Brandle, Jim; Ma, Shengwu; Jevnikar, Anthony; Kohalmi, Susanne E.; Menassa, Rima
Summary: The production of pharmaceutical proteins in plants has made much progress in recent years with the development of transient expression systems, transplastomic technology and humanizing glycosylation patterns in plants. However, the first therapeutic proteins approved for administration to humans and animals were made in plant cell suspensions for reasons of containment, rapid scale‐up and lack of toxic contaminants. In this study, we have investigated the production of human interleukin‐10 (IL‐10) in tobacco BY‐2 cell suspension and evaluated the effect of an elastin‐like polypeptide tag (ELP) and a green fluorescent protein (GFP) tag on IL‐10 accumulation. We report the highest accumulation levels of hIL‐10 obtained with any stable plant expression system using the ELP fusion strategy. Although IL‐10‐ELP has cytokine activity, its activity is reduced compared to unfused IL‐10, likely caused by interference of ELP with folding of IL‐10. Green fluorescent protein has no effect on IL‐10 accumulation, but examining the trafficking of IL‐10‐GFP over the cell culture cycle revealed fluorescence in the vacuole during the stationary phase of the culture growth cycle. Analysis of isolated vacuoles indicated that GFP alone is found in vacuoles, while the full‐size fusion remains in the whole‐cell extract. This indicates that GFP is cleaved off prior to its trafficking to the vacuole. On the other hand, IL‐10‐GFP‐ELP remains mostly in the ER and accumulates to high levels. Protein bodies were observed at the end of the culture cycle and are thought to arise as a consequence of high levels of accumulation in the ER.